Sustainable tourism: a critique of the academic feasibility of the concept - Mika, Mirosław (Turyzm/Tourism, 2015)
The aim of the article is to raise and discuss, according to contemporary research findings, the most important reservations regarding the concept of sustainable (harmonious) tourism development as well as the barriers to the implementation of its principles in practice. The author points to ambiguities in the interpretation of the term ‘sustainability’ and, as a result, the methodological implications for tourism studies including the problem of measuring and evaluating ‘sustainability’ in tourism development processes. In addition it considers the social hostility towards limiting consumption in tourism and the growing climatic, economic and political instability at tourism destinations hindering its implementation of the concept of sustainability. In conclusion, the author proposes a new paradigm for sustainable tourism which does not directly relate to the imperative of harmonious interconnection between differing development goals and values in tourism.